2015
DOI: 10.5897/jaerd2014.0641
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural knowledge management: The case of cattle feed quality improvement in Bure district west Gojjam, Ethiopia

Abstract: The government of Ethiopia gives great attention to livestock development for the country's economy development. Having quality of animal feed is one of the pertinent components of livestock development. To improve the quality and quantity of animal feed in certain locality, farmers should be able to access and use appropriate knowledge for the particular problem at the right time and place. This research was conducted to assess agricultural knowledge management system in relation to improving the quality of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Extension information is generally obtained from extension workers, the mass media (particularly radio and television), printed publications (e.g., newspapers, bulletins, magazines, newsletters, journals, flyers, handbills), and other human groups (i.e., fellow farmers, village heads and traders). Habtemariam et al (2015) stated that rural farmers communicate on their expertise to their neighbours, friends, relatives, and children mostly through informal talk, sharing of experiences, and encouraging other farmers to visit their fields.…”
Section: Sources Of Extension Information Available Tomentioning
confidence: 99%
“…Extension information is generally obtained from extension workers, the mass media (particularly radio and television), printed publications (e.g., newspapers, bulletins, magazines, newsletters, journals, flyers, handbills), and other human groups (i.e., fellow farmers, village heads and traders). Habtemariam et al (2015) stated that rural farmers communicate on their expertise to their neighbours, friends, relatives, and children mostly through informal talk, sharing of experiences, and encouraging other farmers to visit their fields.…”
Section: Sources Of Extension Information Available Tomentioning
confidence: 99%
“…Previous studies in Ethiopia shown that farmers received different agricultural information from different sources using various information pathways. For example, farmers sourced information on improved agricultural technologies from their neighbor in southern Ethiopia (Tewodros and Tesfaye, 2018), extension workers, family members and farmer groups in Tigray region (Gebru et al, 2017) and Agricultural and Rural development office and own experience in Western Amhara region (Habtemariam et al, 2015). Other studies tried to address type of agricultural knowledge and sources that the extension personnel used (Beliyu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Equally, vibrant communication on new ideas and technological innovations for the improvement of agricultural production and productivity is crucial as well. Habtemariam et al (2015) reported that rural farmers transfer their knowledge to their neighbors, friends, relative and children mainly through informal discussion, experience sharing and inviting other farmers to visit their own farms. Sources of agricultural information in the study area can be categorized as organizations and individuals.…”
Section: Introductionmentioning
confidence: 99%